OTOMATISASI SISTEM IRIGASI PERKEBUNAN MENGGUNAKAN METODE TETES DENGAN PHOTOVOLTAIC SEBAGAI SUMBER ENERGI - Mukhlis, Baso; Amin, Nurhani; Fatmawati, Andi; Masarrang, Maryanto (Foristek, 2024)
Red chili is one type of vegetable that is quite important in Indonesia, both as a commodity consumed domestically and as an export commodity. Red chili production in Indonesia is still relatively low. The choice of chili plants in this research is based on the high market demand for chili commodities, however, to meet the demand which continues to increase every year, it is necessary to increase chili production through intensification or extensification. Weather factors have a big influence on the development of chili plants. During the long dry season, chili plants cannot grow well, this is due to the lack of water available for the plant's needs, which increases pest attacks. Another factor is excess soil moisture which can trigger chili plants to rot and die. To make it easier to cultivate chili plants, innovation needs to be carried out to help chili cultivators manage their chili plant cultivation, therefore by using the Plantation Irrigation System Automation tool using the Drip Method with Photovoltaic as an Energy Source it is hoped that this can be an innovation in managing the cultivation of chili plants, especially in controlling soil moisture in chili plants.